Examination and Search of a Defense attorney’s Vehicle - A. О. Shapoval (Bulletin of Kharkiv National University of Internal Affairs)
The author has analyzed some types of investigative (search) actions – examination and search of a defense attorney’s vehicle. Statistical data on the number of conducted investigative (search) actions against defense attorneys have been studied. It has been established that investigative (search) actions against defense attorneys are not always carried out in compliance with the law. It has been argued that most procedural violations occur while conducting investigative (search) actions that involve penetration into a defense attorney’s dwelling or other property. In this regard, it has been concluded that the analysis of legal aspects for conducting examination or search of the defense attorney’s vehicle is currently relevant.